The Dominance of Derivational Suffixes in English News Headlines of the Jakarta Post Online - Nur Hanifatul Zakiyah (International Journal Labs, 2026)
This quantitative descriptive study analyses the dominance and functional application of derivational suffixes in a corpus of 20 English news headlines from The Jakarta Post Online. The research aims to quantify the frequency of suffixes and explain their resulting lexical category changes, aligning with the linguistic constraints of headlinese. A total of 12 instances of class-changing derivational suffixes were identified, demonstrating a systematic reliance on morphological condensation. The analysis reveals two major functional shifts: Nominalisation (V?N) and Adjectivalisation (N?A), with the N?A pattern exhibiting the highest dominance (41.67%), primarily through suffixes like -free,-al,-ian, and -an. The suffix -ing was the most frequent morpheme (33.33%), contributing significantly to Nominalisation. These findings suggest that derivational morphology is a primary structural strategy used to achieve lexical efficiency and informational density in digital journalism.